Multi Verse Optimized Fractional Order PDPI Controller for Load Frequency Control. Issue 5 (3rd September 2022) - Sahoo, Prafulla Kumar; Mohapatra, Srikanta; Gupta, Deepak Kumar; Panda, Siddhartha
ABSTRACT: Multi Verse Optimization (MVO) technique is a newly developed population based algorithm established on the perception of white holes and black holes in a multi-verse for finding out all possibilities of search spaces. This algorithm is applied to tune the proposed Fractional Order Proportional Derivative Proportional Integral (PPDPI) controller of a multi area power system having hydro, thermal, and gas power plants in each area and the system is analysed in two different prospects i.e. with HVDC link and without HVDC link to have realistic situation. The effectiveness of the proposed controller tuned with MVO for load frequency control under small load perturbation (SLP) is compared with other well-known optimization algorithm for the same power system. In this paper, a Fractional-Order Cascade Controller (FOCC) is proposed which is the combination of both the concepts of fractional calculus and cascade control. Cascade connection of FOPI and FOPD are combined in the proposed controller. Change in load and change in system parameters are also incorporated to verify the robustness of the power system where the controllers tuned by the proposed MVO technique. It is observed that the MVO tuned controllers outperformed the performance of recently published TLBO and DE tuned controllers in the area of dynamic performance, stability, and robustness.